Isolation and Identification of Lactobacillus salivarus to be used as probiotic in chickens - Al-Oubaidi, Ebtisam G. A.; Shalash, Ali A.H. (The Iraqi Journal of Veterinary Medicine, 2003)
The study was conducted to isolate and identified Lactobacillus through its biochemical and some biological character The growth inhibition of E. coli (EC) and Salmonella typhimurium (ST) invitro and its sensitivity to pH=3 and its antibiogram were studied. Two isolates of Lactobacillus salivarus (LS) were obtained. The isolated bacteria were taken from the crops of adult chicken, and cultured on M.R.S. broth, they were Gram positive bacilli, negative for catalase and amonia production from Arginin. The first isolate showed inhibitory zone of 22 mm diameter against (EC) and 19 mm. against (ST) The second isolate showed inhibitory zone of 1mm diameter against (EC) and did not show an inhibitory zone against (ST) Adhesive ability of the first isolate was strong while that of the second isolate was weak. The first isolate showed growth on Rogosa media in pH=3 and It was resistant to the following antimicrobial drugs: Enrofloxacine, Ciprofloxacine, Norfloxacine, Flumequine, Doxycycline, Tetracycline, Sulfanomide, Furaltidone, and sensitive to Ampicillin, Neomycin, Chloramphenicol. It was concluded that the first isolate of Lactobacillus salivarus could be successfully used as probiotic in chickens.